Present situation of cassava production and the research and development strategy in Vietnam - Pham, Van Bien; Hoang, Kim; Wang, Joel J.; Howeler, Reinhardt H. (International Center for Tropical Agriculture, 2001)
Vietnam produces annually more than 2 million tonnes of cassava fresh roots and is ranked 13th in terms of cassava production in the world. In Vietnam cassava has great potential both for domestic consumption and for export. In North Vietnam, cassava is grown for food and animal feed by small farmer households. However, in South Vietnam cassava has become a cash crop and is an important raw material for cassava processing factories, which have a total annual processing capacity of one million tonnes of fresh roots. The main constraints in cassava production in Vietnam are fluctuating prices as well as marketing problems, and slow adoption of new varieties and improved technologies in remote areas. Low soil fertility in cassava growing areas is also an important problem, as is the lack of processing facilities. Cassava research in Vietnam has made remarkable progress since 1988 when Vietnam began its cooperation with CIAT and started taking part in the Asian Cassava Research Network. Further progress in cassava production was achieved when Vietnam established its Cassava Research and Extension Network, in close cooperation with starch processing factories, especially Vedan Vietnam Enterprise Corp. Ltd. New high yield cassava varieties (KM94, KM60 SM937-26, KM98-1, KM95-3, KM95) and more sustainable production practices (fertilizer application, intercropping or rotation with beans or peanut, erosion control and weed control) has increased the economic effectiveness of cassava production, especially in the Southeastern region. In order to transfer new technologies to cassava households, Farmer Participatory Research (FPR) was conducted in mountainous and hilly areas of North Vietnam. The first phase of this project was quite successful. Presently, the second phase has expanded into the Central Coastal and Southeastern Regions. The use of cassava roots and leaves for animal feed are also being studied. Biotechnology has initially been applied in lysine and modified starch processing. Our cassava research strategy for the future consists of the following: further advances in cassava breeding and in production practices; improving soil fertility of cassava growing areas; planning and establishing production areas for processing factories; developing post-harvest technologies, and expanding markets for cassava products. The development of high starch and high yield varieties and the adoption of sustainable cassava production practices will help to maintain total cassava production while the growing areas can be reduced. This will create a strong incentive for the development of cassava industrial processing and diversification of end-products, in order to satisfy the increasing demand for cassava-based products by our people.